GAME EDUKASI AUGMENTED REALITY BERBASIS RME (REALISTIC MATHEMATICS EDUCATION) UNTUK MENINGKATKAN COMPUTATIONAL THINKING SISWA - Odhitya Desta Triswidrananta; Agung Nugroho Pramudhita; Elita Mega Selvia Wijaya (Universitas Tribhuwana Tunggadewi, 2024)
This research addresses the common problem in mathematics education in Indonesia, which is the students' difficulties, as reflected in Indonesia's declining ranking in the Program for International Student Assessment (PISA). The research aims to create an innovative Augmented Reality (AR) Educational Game based on the Realistic Mathematics Education (RME) approach to improve students' understanding of the spatial geometry mathematics subject at the elementary school level. AR technology allows students to interact with mathematical objects in real-world contexts using Android devices. This game is designed to make mathematics more engaging and relevant to elementary school students. The research was conducted at Purwantoro 1 Public Elementary School in Malang City over four months, following the Game Development Lifecycle (GDLC). The test results showed an n-gain improvement of 0.71, indicating a positive impact of the game's development on students' learning outcomes.